Polyploid giant cancer cells and ovarian cancer: new insights into mitotic regulators and polyploidy. Issue 2 (25th May 2021) - Richards, JoAnne S; Candelaria, Nicholes R; Lanz, Rainer B
Abstract: Current first-line treatment of patients with high-grade serous ovarian cancer (HGSOC) involves the use of cytotoxic drugs that frequently lead to recurrent tumors exhibiting increased resistance to the drugs and poor patient survival. Strong evidence is accumulating to show that HGSOC tumors and cell lines contain a subset of cells called polyploidy giant cancer cells (PGCCs) that act as stem-like, self-renewing cells. These PGCCs appear to play a key role in tumor progression by generating drug-resistant progeny produced, in part, as a consequence of utilizing a modified form of mitosis known as endoreplication. Thus, developing drugs to target PGCCs and endoreplication may be an important approach for reducing the appearance of drug-resistant progeny. In the review, we discuss newly identified regulatory factors that impact mitosis and which may be altered or repurposed during endoreplication in PGCCs. We also review recent papers showing that a single PGCC can give rise to tumors in vivo and spheroids in culture. To illustrate some of the specific features of PGCCs and factors that may impact their function and endoreplication compared to mitosis, we have included immunofluorescent images co-localizing p53 and specific mitotic regulatory, phosphoproteins in xenografts derived from commonly used HGSOC cell lines. Abstract : Cytotoxic drugs frequently used in ovarian cancer treatment impact tumor cell cycle progression and the emergence of polyploid cells where genetic and epigenetic events ultimately lead to drug-resistant diploid progeny.